ANALISIS EKOLOGI BERWAWASAN GENDER (ECOFEMINISM) DALAM KARYA SASTRA PARA SASTRAWAN LAMONGAN - Kiki Astrea; Anisa Ulfah (HUMANIS: Jurnal Ilmu-Ilmu Sosial dan Humaniora, 2019)
The purpose of this study is the discovery of (1) the influence of political ecological values (2) the influence of cultural ecological values (3) the influence of social ecological values, and (4) the influence of the ecological values of imperialism heritage. The data in this study are data about (1) the influence of political ecological values (2) The influence of cultural ecological values (3) The influence of social ecological values, and (4) the influence of the ecological values of imperialism heritage. Data sources are obtained from documentation and interviews. The data collection techniques are carried out with documentation and interviews. Data analysis techniques use interactive techniques. Data validation uses triangulation, both triangulation of theories, data, and methods. The research findings can be described include: (1) the influence of political ecological values (2) The influence of cultural ecological values (3) The influence of social ecological values, and (4) the influence of the ecological values of imperialism inheritance in the literary text writer in Lamongan